Plang Edukasi Estetik: Inovasi Visual untuk Meningkatkan Kesadaran dan Daya Tarik Wisata Berwawasan Lingkungan - Maya Apriani; Muh ramli (Macoa : Jurnal Pengabdian kepada Masyarakat, 2026)
Abstract This community service activity was carried out at Ceppa Petabu Beach, Dusun 5, Galeso Village, Wonomulyo District, Polewali Mandar Regency, West Sulawesi. The main objective was to increase the awareness and concern of local communities and tourists toward environmental cleanliness through a visual innovation in the form of aesthetic educational signboards. This program was motivated by the growing waste problems in coastal tourism areas, which are largely caused by visitors’ low awareness of environmentally friendly behavior. The implementation methods included participatory discussions with village officials and the community, hands-on practice in designing and installing educational signboards, and observational evaluations of visitor responses. The results showed an increase in community participation in maintaining environmental cleanliness, improvement in local residents’ skills in creating creative educational media, and behavioral changes among tourists in disposing of waste properly. Furthermore, the educational signboards, which also serve as aesthetic photo spots, successfully enhanced the tourism appeal and strengthened the image of Ceppa Petabu Beach as an environmentally conscious destination. This activity has provided tangible benefits to the community, increased ecological awareness, and become a model for the development of community-based educational tourism that is creative and sustainable.